Knowledge of Low Back Pain among Primary School Teachers - Josep Vidal-Conti (MDPI AG, 2021)
Low back pain (LBP) is a prevalent musculoskeletal disease that affects a large percentage of the working population, including teachers. The World Health Organization has identified the school as an effective environment for improving child health. For this reason, the figure of the teacher is a fundamental piece in the process of knowledge acquisition about postural education and prevention of LBP among schoolchildren. The present study aims to determine the knowledge of postural education and back pain prevention among primary school teachers. This cross-sectional study evaluated 85 primary school teachers from Majorca (Spain), of whom 17.6% were physical education teachers and 82.4% were classroom teachers. The study was based on two different structured and self-administered questionnaires to investigate into specific knowledge about LBP: Low Back Pain Knowledge Questionnaire (LKQ) and COSACUES-AEF Questionnaire. The results demonstrated a lifetime prevalence of LBP of 96.5% with significant differences determined by sex. The knowledge of participants about LBP was 17.3 in LKQ (range scale 0–24) and 4.3 in COSACUES (range scale 1–10). In conclusion, the teachers knowledge is insufficient to carry out an efficient and useful health promotion program among schoolchildren to prevent LBP.